Elaboration and characterization of environmental properties of TiO2 plasma sprayed coatings - L. Toma; N. Keller; G. Bertrand; D. Klein; C. Coddet (International Journal of Photoenergy, 2003)
Titanium dioxide (TiO2) is an attractive material for numerous technological applications such as photocatalytical applications. These materials can in some conditions have the ability to allow the environmental purification of air and water by the decomposition and removal of harmful substances, such as volatile organic compounds (VOC), benzene compounds, NOx, SO2, etc. Our work was focused on the elaboration and the evaluation of the environmental properties of titanium dioxide coatings by plasma spray techniques. The principle of plasma spraying consists by the injection in an enthalpic source (plasma) of the powder of one material to be sprayed. The molten powder is transported and accelerated by the plasmaproducing gas flow and crushed on the target substrate, where the particles of material solidify with high speeds, thus forming the coating. The advantages of thermal spraying consist in the fact that the coating has stability, durability, adherence and cohesion. For this study, the initial powder material was an anatase TiO2. The photocatalyst coating was realized by a few kinds of thermal spray method: gas flame, APS (atmospheric plasma), VPS (vacuum plasma) and HVOF (high velocity oxygen fuel). The microstructures of the deposits, as a function of the coating process, are analysed by optical microscopy, scanning electronic microscopy, and the X-rays diffraction. To carry out the step of validation of these surfaces for their environmental functionalities, we used a control test process for the photocatalytic effectiveness with respect to nitrogen oxides. For that an original test chamber has been developed. Ultraviolet rays irradiated the coating specimens and the efficiency of NOx elimination has been controlled using a gas analyser. We studied the photocatalytical properties of different obtained coatings as a function of various parameters (porosity, thickness, ratio anatase/rutile).